Identifikasi Zat Pewarna Rhodamin B Dan Methanyl Yellow Pada Kerupuk Yang Dijual Di Pasar Beringharjo Yogyakarta Tahun 2016 - Rahayu, Muji; Mahmuda, Yulia Irma (POLTEKKES KEMENKES YOGYAKARTA, 2016)
â€œKerupukâ€ is one kindof complementary foods preferred by many people. â€œKerupukâ€ can add the taste of the food and can be eaten as a snack. Consumers need to be cautious in consuming â€œkerupukâ€, because there are still many â€œkerupukâ€ made with prohibited dyes, especially Rhodamine B and Methanyl yellow. The presence of rhodamine B and methanyl yellow in colored â€œkerupukâ€ can cause the color look unnaturally strong. Rhodamine B and methanyl yellow can cause health problems if they are consumed. This research aims to determine the percentage of rhodamine B and methanyl yellow which is used on â€œkerupukâ€ sold in Beringharjo Yogyakarta Year 2016. The samples used in this study are 27 samples, which consist of â€œkerupuk bawangâ€ and â€œkerupuk taroâ€ and are acquired in Beringharjo Yogyakarta. â€œkerupuk bawangâ€ and colorful â€œkerupuk taroâ€ are separated by color, only yellow and red ones are taken. The samples were tested for rhodamine B and methanyl yellow qualitatively using Thin Layered Chromatography (TLC) method. Results of laboratory tests show that 2 of 15 samples tested contain rhodamine B (13.3%) and none of 12 samples contain methanyl yellow